New Methodological Approaches to Review Governance and Financing Arrangements in Vocational Education and Training (VET) and Skill Systems: A Data Collection Tool (DCT) 4.0 for Facilitating Self-Assessment Processes - Galvin Arribas, J. Manuel (HAPSc Policy Briefs Series, 2020)
The European Training Foundation (ETF) is more than aware that effective -good multilevel- governance arrangements in Vocational Education and Training (VET)-and Skill policies-is key for having sound skills in the labour market. The ETF developed new Data Collection tool 4.0 (DCT) to implement self-assessments working with partner countries (PCs) in governance and financing arrangements involving, at least, seven different categories of policy stakeholders (e.g. governmental actors-public servants-, social partners, private actors, key experts). This -innovative- tool contains 65 indicators for self-assessing seven governance- and financing- functions including institutional coordination mechanisms (e.g. strategic and legislative framework, management of public-private partnerships, VET providers network, evaluation, research and data analysis provision, councils/committee’s system etc.). The DCT 4.0 has been piloted in 5 ETF PCs (Albania, Jordan, Kazakhstan, Moldova and Uzbekistan). The results might inform further policy development driven by governance and financing arrangements/issues in ETF PCs (or perhaps, beyond). Further, this tool for policy analysis could inspire advisory processes focusing on how to support systemic reforms and/or carry out monitoring implementation-and/or policy review-, based on different types of governance and financing arrangements. The pilot experience developed in COVID 19 times, confirmed that online facilitation is a good way to get good results. However, the human touch factor is essential to facilitate such self-assessment in more impactful way as it could be embedded in real time into current policy dialogue strategies in the countries.